Impact of Covid-19 on the Financial Sector Indices - D, Bhuvaneshwari; P, Radhika K (International Research Journal of Business Studies, 2021)
This study is an attempt to assess the impact of Covid-19 and the lockdown pronounced thereof on the Nifty sectoral indices with specific reference to the financial sector indices owing to their significance in the economy. The OLS regression, Granger Causality and Impulse Response Function were estimated to measure the changes in the future responses of Nifty 50 to the changes in the select sectoral indices, namely, Nifty Bank, Nifty Financial Services and Nifty Private Banks and Nifty PSU Banks for the period consisting two sub-periods, i.e., the first sub-period from April 2019 to March 2020 are assumed as the preCovid-19 period and the second sub-period from April 2020 to March 2021 is assumed as the period during Covid-19. The results indicated that the shock of the Covid-19 had an impact on the financial sector indices in India during the Covid-19 period.